Non–Small-Cell Lung Cancer: Real-World Cost Consequence Analysis. (20th October 2021) - De Polo, A; Buja, A; Pasello, G; Bortolami, A; Zorzi, M; Schiavon, M; Marchetti, M; Baldo, V; Rugge, M; Conte, PF
Abstract: Background: The present work aimed at conducting a real-world data analysis on the management costs and survival analysis comparing data from non-small-cell lung cancer (NSCLC) cases diagnosed in the Veneto region before (2015) and after (2017) the implementation of a regional diagnostic and therapeutic pathway including all new diagnostic and therapeutic strategies. Methods: This study considered 254 incidental cases of NSCLC in 2015 and 228 in 2017 within the territory of the Padua province (Italy), as recorded by the Veneto Cancer Registry. Tobit regression analysis was performed to verify if total and each item costs (2 years after NSCLC diagnosis) are associated with index year, adjusting by year of diagnosis, sex, age, and stage at diagnosis. Logistic regression models were run to study overall mortality at 2 years, adjusting by the same covariates. Results: The 2017 cohort had a lower mortality odd (odds ratio, 0.93; P = .02) and a significant increase in the average overall costs (P = .009) than the 2015 cohort. The Tobit regression analysis by cost item showed a very significant increase in the average cost of drugs (coefficient = 5, 953, P 5 .008) for the 2017 cohort, as well as a decrease in the average cost of hospice care (coefficient = -1, 822.6, P = .022). Conclusions: Our study showed a survival improvement for patients with NSCLC as well as an economic burden growth. Physicians should therefore be encouraged to follow new clinical care pathways, while the steadily rising related costs underscore the need for policymakers and health professionals to pursue the most rational utilization of public resources. Key messages: Our work underscores the importance of real-world assessment of costs in oncology, especially in case of a disease like NSCLC, which has such a high impact on treatment costs and patient outcomes. New therapies prolong survival for patients with NSCLC but their sustainability reminds of the importance of prevention: the earlier the diagnosis, the longer the survival and the lower the costs.